The Impact of Cigarette Smoking on The Efficiency of Local Anesthesia Among Libyan Patients During Simple Dental Procedures in Tripoli-Libya - Khalid Milad; Shahir Ghiath; Mohmmed Sehaib (AlQalam Journal of Medical and Applied Sciences, 2025)
Cigarette smoking alters drug pharmacokinetics, including the effects of local anesthetics like lidocaine, commonly used in dentistry. This Libyan-based prospective case-control study compared 42 smokers and 42 non-smokers receiving 2% lidocaine for dental procedures, assessing anesthesia amount, onset time, duration, and chief complaints. Data were analyzed using SPSS v.27 and JAMOVI, with significance at p < 0.05. Results showed smokers required significantly more anesthesia (p = 0.005), had delayed onset (p = 0.024), and shorter anesthetic duration (p = 0.001) than non-smokers. Chief complaints also differed significantly (p < 0.01). A moderate positive correlation existed between anesthesia dosage and both smoking duration (rho = 0.368, p = 0.016) and daily cigarette consumption. Conversely, anesthetic duration had a strong negative correlation with daily cigarette intake (rho = -0.445, p = 0.003), but no link with smoking duration. In conclusion, smoking increases local anesthetic requirements, prolongs onset, and shortens effectiveness, with dosage directly related to smoking duration and daily consumption. Dental practitioners should adjust anesthesia protocols for smokers to ensure optimal pain management.